Análise da demanda evapotranspirométrica do semi-árido do estado de Sergipe - Prado, Edilton Ferreira (2006)
The agricultural development demands new strategies, in the sense of to potentiate the productivity and to minimize the risks in the production. The irrigation handling is a technique that seeks to supply the hydric demand of the crop. The irrigation handling should be associated to the preservation of the hydric resources and of the environment, allowing maintainable benefits in the agricultural explorations. To understand and to predict the amount of necessary water in an irrigation accurately and perfected, the continuous soil-plant-atmosphere should be considered as a dynamic system, physically integrated, where the transport processes happen in an interactive way. In this, the meteorological factors of surface control the force of hydric demand, then a monitor system and control based on measurements, in real time, of linked parameters to the continuous soil-plant-atmosphere should be used to determine the hydric needs of the crop and to establish strategies of irrigation handling, seeking to improve and to rationalize the use of the water and of the energy with improvement of productivity of the crop. In the irrigated perimeters of the state of Sergipe/Brazil, the water has almost always been applied in deficit or excess, without considering the relative aspects to the climate, to the characteristics physical-hydric of the soil and to the fenological characteristics of the crop, resulting in immeasurable losses of production, of water and of energy. That project has for objective to esteem the evapotranspiration demand (reference evapotranspiration - ETo) starting from meteorological variables registered in conventional and automatic meteorological stations, in the semi-arid of the state of Sergipe/Brazil, comparing the results obtained among the estimate methods, to determine the viable methods of application in the area.